علاقة الدولة الإسلامية بغير المسلمين في رأي رشيد رضا من خلال تفسيره المنار - Abdoul Karim Toure; Mohd. Fauzi Mohd. Amin; A. Irwan Santeri Doll Kawaid; Syed Najihuddin Syed Hassan; Zulhilmi Mohamed Nor; Norullisza Khosim (Universiti Sains Islam Malaysia, 2024)
Islam is a religion of violence, spread by the sword, and the Islamic State's relationship with other nations and with non-Muslims is but war and fighting. These are the common words to portray Islam and the Islamic State. What is the reality of the ground in the opinion of Mohammad Rashid Rida through his interpretation of al-Manar? This study attempted to answer these questions through his interpretation of the verses ordering Muslims to fight non-Muslims, and verses prohibiting Muslims to having a good relationship with non-Muslims, and verses allowing Muslims to having good relationship with non-Muslims. The study concluded that in the opinion of Mohammad Rashid Rida, peace is the priority in the relations between the Islamic State and others, war and fighting is for protection and to defend its right. The method upon which the study is based is inductive method. The researchers elaborated in the study verses in which Rashid Rida in his Tafsir al-Manar